Study on the creation and validation of educational technology for caregivers of children with distal forearm fracture (Research, Society and Development, 2022)
Introduction: More than 40% of girls and more than 50% of boys suffer at least one fracture during childhood and adolescence, with distal forearm fractures being the most common and accounting for up to a third of all pediatric fractures. The use of educational instruments allows the patient and caregiver to overcome their difficulties and obtain greater autonomy in the care process for better health conditions and quality of life. Objective: To develop and validate a primer-type educational technology to mediate physical therapy care for caregivers of children with distal forearm fractures, to be used both in the hospital and in the home environment. Materials and methods: Methodological development study for the creation and validation of educational technology, carried out in the city of Santarém-Pará, from January to August 2021. The creation of educational technology was based on scientific literature. In the content validation, 10 specialist judges participated, and in the apparent one, 15 caregivers, who answered a questionnaire with 3 and 5 blocks, respectively. For statistics, the Content Validity Index was calculated using the BioEstat 5.3 software. Results: The Content Validity Index of each blog and the overall questionnaire reached a value above that proposed by the study. Conclusion: The educational technology produced has statistical validity of its content by expert judges and caregivers.